A comprehensive experimental investigation on the PFI spray impingement: Effect of impingement geometry, cross-flow and wall temperature. (August 2019) - Li, Yaoting; Huang, Yongcheng; Yang, Shangsheng; Luo, Kun; Chen, Rixin; Tang, Chenglong
Abstract: In this work, an experimental study on the effects of the impingement geometry, the cross-flow intensity and the wall temperature on the characteristics of an impinging port fuel injection (PFI) spray was conducted. The transient development of the impinging spray was recorded by a high-speed camera with Mie scattering. Based on the high-speed images, the spray tip penetration ( S ) and the impinged spray height ( Hw ) were obtained. The results show that with the increase of the impingement distance ( Lw ), S increases and Hw decreases at the same time after the impingement. As the impingement angle ( θw ) increases, S decreases while Hw first increases and then decreases. With the increase of the cross-flow velocity ( Uc ), less part of the spray impinges onto the wall, and S significantly increases. As the wall temperature ( Tw ) rises, S does not show much variation. However, Hw increases gently for Tw lower than 420 K, and it increases sharply for Tw higher than 420 K due to the Leidenfrost mechanism. The effects of the above factors ( Lw, θw, Uc, Tw ) on S and Hw were finally evaluated and compared through the introduction of a contribution index.